Imunoterapie nádorů dolní části trávicí trubice - Tomášek, J; Kiss, I (Klinicka onkologie, 2017)
BACKGROUND: The lower part of the digestive tract includes the large intestine, rectum and anus. Treatment algorithms of cancers in these localities have significant differences in both early and advanced stages. The vast majority of metastatic cases are incurable. A few years ago, it was generally accepted that gastrointestinal tumors are poorly immunogenic and modern immunotherapy would not work in gastrointestinal cancers. The breakthrough has become the recognition of the mismatch repair system (MMR) that affects the microsatellite instability (MSI) and its role in the development of colorectal carcinoma (CRC). Metastatic colorectal carcinoma (mCRC) with defect MMR (dMMR) and MSI-H, resp. is immunogenic and can be a target of modern imunotherapy directed on the PD1/PD-L1 axis. Such a treatment can improve prognosis and life quality od patients with mCRC MSI-H. Immunotherapy effectiveness was shown also in a subgroup of patients with a BRAF mutation where the effectiveness of existing systemic treatment is low. The proven predictive factor is dMMR/MSI-H. PD-1 expression does not have this significance. Results of clinical studies with nivolumab and pembrolizumab result in the inclusion of these drugs in mCRC treatment algorithms. Phase II study shows nivolumab effectiveness also in pretreated metastatic anal cancer. PURPOSE: An overview of basic information on the possibilities of immunotherapy in CRC and anal cancers.Key words: cancer immunotherapy - checkpoint inhibitors - colorectal cancer - anal cancer - nivolumab - pembrolizumab Supported by MH CZ - DRO (MMCI, 00209805) I declare that, in connection with the abovementioned contribution, which I am an author, I have a conflict of interest with the following companies: BMS, Roche, Merck, Amgem and Bayer. The author declares he has no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 7. 9. 2017Accepted: 5. 11. 2017.
Keywords: Microsatellite Instability; oprava chybného párování bází DNA; DNA Mismatch Repair; antigeny CD279; Humans; mikrosatelitní nestabilita; antigeny CD274; kolorektální nádory; Programmed Cell Death 1 Receptor; lidé; imunoterapie; Immunotherapy; B7-H1 Antigen; Anus Neoplasms; Colorectal Neoplasms; nádory anu